Appraising the Fuel Price and Financial Risk Components Effects on Sales in the South African Automotive Industry - Habanabakize , Thomas; Dickason-Koekemoer, Zandri (Acta Universitatis Danubius. Œconomica, 2022)
The automotive industry is one of the manufacturing sub-sectors that play a vital role in countries' economies. However, this industry is not exempt from the effect of fuel price and financial risk components. This study investigates the effect of fuel price and financial risk components on the South African motor trade sales for the period 2008-2021. The research is built on previous work and research on the linkage between fuel price and country risks. Auto-regression Distributed Lag (ARDL) model was applied to monthly financial data (exchange rate, interest rate), fuel price and motor trade sales. Findings suggested the presence of a long-run relationship among these variables. Findings suggested the presence of a long-run relationship among these variables. It was found that both interest rate and exchange rate have negative impacts on long-run motor trade sales. Nonetheless, the fuel price was found to be statistically insignificant to influence motor-trade sales in the long run. The results also indicated that both interest rate and exchange rate cannot impact motor trade sales in the short run. Based on these results, the study stressed that policies that strengthen and stabilise the South African currency (exchange rate) are imperative to increase sales in the automotive industry and economy in general. Easing and lowering interest rates can also assist in boosting motor trade sales irrespective of the fuel price. The paper uniquely provides the interactions between fuel price, financial risk and sales within the South African automotive industry. It also suggests strategies that can be implemented to improve sales within the aforementioned industry.